Configurational Entropy Driven High‐Pressure Behaviour of a Flexible Metal–Organic Framework (MOF). Issue 2 (12th November 2020) - Vervoorts, Pia; Keupp, Julian; Schneemann, Andreas; Hobday, Claire L.; Daisenberger, Dominik; Fischer, Roland A.; Schmid, Rochus; Kieslich, Gregor
Abstract: Flexible metal–organic frameworks (MOFs) show large structural flexibility as a function of temperature or (gas)pressure variation, a fascinating property of high technological and scientific relevance. The targeted design of flexible MOFs demands control over the macroscopic thermodynamics as determined by microscopic chemical interactions and remains an open challenge. Herein we apply high‐pressure powder X‐ray diffraction and molecular dynamics simulations to gain insight into the microscopic chemical factors that determine the high‐pressure macroscopic thermodynamics of two flexible pillared‐layer MOFs. For the first time we identify configurational entropy that originates from side‐chain modifications of the linker as the key factor determining the thermodynamics in a flexible MOF. The study shows that configurational entropy is an important yet largely overlooked parameter, providing an intriguing perspective of how to chemically access the underlying free energy landscape in MOFs. Abstract : By combining high‐pressure powder X‐ray diffraction and molecular dynamics simulation we gain insight into the microscopic chemical factors that determine the high‐pressure macroscopic thermodynamics of two flexible pillared‐layer MOFs, identifying configurational entropy as originating from side‐chain modifications as the determining factor of the macroscopic thermodynamics.